PENGARUH KETERLIBATAN PELANGGAN DAN KEPERCAYAAN MEREK TERHADAP KEPUTUSAN PEMBELIAN PRODUK MELALUI MINAT BELI SEBAGAI VARIABEL INTERVENING (STUDI PADA AKUN INSTAGRAM EIWA) - Athira Setira Adil; Muhammad Asdar; Muhammad Ismail (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2018)
Firms that want to survive have to compete more in formulating the strategy of offering and selling the company's products, and advanced companies are companies that are able to keep up with the times, customer behavior changes, and of course technological advancement. This research aims to know to know the influence of customer involvement and brand trust of buying interest and purchasing decisions on Eiwa instagram account. The type of research used in this study is quantitative approach. The quantitative approach bases the study of empirical rational principles. The quantitative approach bases the study of empirical rational principles. Before doing research the researcher must find the problem and hypothesis to be tested based on specified criteria and path analysis tool that is Smart PLS to know variable relation. The result of the research shows that for direct influence, customer involvement has a positive and significant effect on buying interest, brand trust has positive but not significant effect on buying interest, customer involvement has a positive and significant effect on purchasing decision, brand trust has positive and significant influence on purchasing decision product, while buying interest has a positive and significant effect on purchasing decision of Brand Eiwa product. As for indirect influence, buying interest may mediate the influence of Customer Engagement on product purchasing decisions positively and significantly while Buy Interest can not mediate the influence of Brand Trust on Brand Eiwa product purchase decision positively and significantly.